2021
DOI: 10.1111/eje.12704
|View full text |Cite
|
Sign up to set email alerts
|

Learning of paediatric dentistry with the flipped classroom model

Abstract: The teaching methodology in dentistry is undergoing great changes. It is necessary for students to develop critical thinking and know how to solve problems. Students must acquire the ability to self-direct information search strategies, which are necessary to correctly develop their professional practice. 1,2 A relatively recent learning strategy that helps students improve these aspects is the so-called flipped classroom (FC). According to Abeysekera and Dawson, FC is defined as a set of pedagogical approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…The results showed that the ipped method was more effective. This result is in line with the research of Gallardo et al, Wang et al, and Ozcan, who compared the nal scores of dental students in the ipped classroom and face-to-face training (49)(50)(51).…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the ipped method was more effective. This result is in line with the research of Gallardo et al, Wang et al, and Ozcan, who compared the nal scores of dental students in the ipped classroom and face-to-face training (49)(50)(51).…”
Section: Discussionsupporting
confidence: 90%
“…In response to the indications of the students, in this research, we wanted to incorporate another digital tool (i.e., Edpuzzle) through which they could view the videos and allow feedback between student and teacher on the selected platform. In addition, in this study we analysed both theoretical and practical learning, since this is the main objective of these preclinical classes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the 2018–2019 academic year, an educational innovation project was carried out on the incorporation of FL in the preclinical practices of Paediatric Dentistry II in the Dentistry Degree at the UCM. The results indicated that the visualisation of videos through the CV (Moodle) before the preclinical practices improved the acquisition of theoretical knowledge and was very satisfactory for the students [ 5 ]. However, in the satisfaction survey, 85% of the students answered that trying other platforms more suitable to FL for viewing the videos would be very useful and interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the flipped classroom has been introduced in different fields of dentistry. Students considered it a more fun interactive and collaborative technique than the traditional class [ 13 , 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the noted disadvantages of this teaching method is the requirement of an Internet connection [ 11 ]. Two studies on flipped classrooms in the field of pediatric dentistry showed that students were satisfied with this method [ 12 , 13 ], providing the notable advantages of availability and access to online content and course materials, clickers to test knowledge in preparation for an exam, and in-class group discussions with the help of students questionnaires [ 12 ]. The results of a study with a flipped classroom on the physiology of the autonomic nervous system indicated that students spent more time learning, understood the content better, performed better in assessments, and preferred this method to a traditional lecture [ 14 ].…”
Section: Introductionmentioning
confidence: 99%